Preparation method and application of super-hydrophobic SiO2 hydrogel for zinc-copper-titanium alloy anodic oxide film surface
The superhydrophobic SiO2 hydrogel film prepared and modified by the two-step acid-base method solves the problem of insufficient superhydrophobicity and corrosion resistance on the surface of zinc-copper-titanium alloy, and achieves high-efficiency corrosion resistance and superhydrophobicity improvement of the material.
Patent Information
- Application Number
- CN202410027441.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-01-08
AI Technical Summary
The prior art is difficult to effectively improve the superhydrophobicity and corrosion resistance of zinc-copper-titanium alloy surfaces, especially in applications in marine environments.
Superhydrophobic SiO2 hydrogels were prepared by acid-base two-step method, and the use of PDMS-OH and PMHS modifiers were replaced by ethanol solvents and the use of PDMS-OH and PMHS modifiers to form a SiO2 hydrogel film with a porous structure and low surface energy, and coated on the zinc-copper-titanium alloy anodized film.
It significantly improves the corrosion resistance and surface properties of the zinc-copper-titanium alloy anodized film, gives it self-cleaning and anti-fouling functions, and extends the service life of the material.
Smart Images

Figure CN117947482B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of surface treatment of zinc-copper-titanium alloy anodic oxide films, and in particular to a super-hydrophobic SiO 2 The invention relates to a preparation method and application of a hydrogel. Background Art
[0002] In order to improve the corrosion resistance and wear resistance of the zinc-copper-titanium alloy surface, surface processes such as phosphating, passivation and anodizing are usually used. These surface processes can effectively improve the surface properties of zinc-copper-titanium alloy and extend its service life. Among them, phosphating is to immerse the zinc-copper-titanium alloy in a phosphate-containing solution, and a phosphating film is formed after a certain period of time to enhance the surface hardness and corrosion resistance. Passivation improves corrosion resistance by forming an oxide film on the surface of the zinc-copper-titanium alloy. Anodizing uses electrolysis to form an oxide film on the surface of the zinc-copper-titanium alloy to improve wear resistance and corrosion resistance.
[0003] Among the three methods of zinc-copper-titanium alloy surface treatment, anodizing is the most environmentally friendly method, because anodizing does not require the use of toxic chemicals, and can reduce energy consumption and wastewater generation by controlling current and voltage. Therefore, when selecting a zinc-copper-titanium alloy surface treatment method, the present invention gives priority to anodizing as an environmentally friendly passivating agent and treatment process to reduce the impact on the environment.
[0004] Anodizing the surface of zinc-copper-titanium alloy is a surface treatment technology. Its principle is to apply current to the anode of the alloy in an electrolyte to form an oxide film on its surface. This oxide film can improve the corrosion resistance and wear resistance of the alloy, and also increase the aesthetics of its surface. A lot of heat will be generated during the anodizing process, so the electrolyte needs to be cooled and circulated. At the same time, the formation of the anodized film requires a certain amount of time, usually ranging from a few minutes to tens of minutes. In addition, the quality of the anodized film is also related to the purity and concentration of the electrolyte, and the electrolyte needs to be replaced and the equipment cleaned regularly. In specific applications of anodized films, coating Si0 2 Hydrogels can provide some additional functions or properties. 2 The hydrogel has the characteristics of high water absorption, high water retention and good biocompatibility. 2 Hydrogel can improve the surface lubricity and wear resistance of the anodic oxide film, thereby extending the service life of the material. 2 Hydrogel needs to choose the right Si0 2 Hydrogel materials and coating processes are used to ensure compatibility and stability with the anodized film. 2 Hydrogels may also affect the surface morphology and properties of the anodized film, so the anodized film needs to be properly surface treated and modified before coating.
[0005] The sol-gel process is a wet chemical preparation method, in which metal alkoxides or inorganic salts are hydrolyzed and polycondensed in a liquid state to form a sol, and then cross-linked and polymerized between the sol particles to form a gel, and finally the desired material is obtained through drying, sintering and other treatments. The process involves the formation of a sol, which is then transformed into a gel through a gelation process, and finally a solid material is formed through heat treatment. This process usually involves the hydrolysis and polymerization of metal organics. The advantages of the sol-gel process include: first, the reaction conditions are mild and can be carried out at room temperature and pressure; second, the product has good uniformity and high purity; third, the reaction process is controllable, and uniform doping at the molecular level can be achieved. Therefore, when selecting a surface treatment method for zinc-copper-titanium alloy, the present invention gives priority to using the sol-gel process to prepare Si0 2 Hydrogel.
[0006] Hydrothermal sealing is often used to form a protective film on the surface of the material to prevent corrosion and improve the durability of the material. Hydrothermal sealing is a method of sealing or filling the pores in the material using hydrothermal reaction under high temperature and high pressure conditions. This method is usually used in material preparation, nanomaterial synthesis, and some chemical reactions. The principle of hydrothermal sealing is to immerse the material in high temperature and high pressure water to form a dense oxide film on its surface, thereby protecting the material. The advantage of hydrothermal sealing is that a dense oxide film can be formed on the surface of the material, which can achieve the effect of high temperature and high pressure under relatively mild conditions, help to form a more uniform pore structure, and improve the corrosion resistance and durability of the material. This method is widely used in the fields of catalysts, adsorbents, electrode materials, etc. to improve the performance and application range of the material. In addition, this technology can also reduce environmental pollution. Therefore, when selecting the surface treatment method of the zinc-copper-titanium alloy oxide film, the present invention gives priority to the use of prepared Si0 2 Hydrogel is used to coat and seal the zinc-copper-titanium alloy oxide film.
[0007] Choosing a suitable surface treatment method to improve the superhydrophobicity and corrosion resistance of zinc-copper-titanium alloy needs to be considered: First, the surface structure. Different surface treatment methods will form different structures on the surface of zinc-copper-titanium alloy, such as micropores, nanostructures, etc. These structures will affect the superhydrophobicity and corrosion resistance of the material. Therefore, it is necessary to select a surface treatment method that can form a suitable surface structure. Second, chemical composition. The chemical composition of zinc-copper-titanium alloy will also affect its superhydrophobicity and corrosion resistance. For example, adding certain elements can improve the corrosion resistance of the material. Therefore, it is necessary to select a surface treatment method that can match the chemical composition of zinc-copper-titanium alloy. Third, cost-effectiveness. Different surface treatment methods have different costs, and cost-effective methods need to be selected. Fourth, environmental impact. Some surface treatment methods may cause pollution to the environment, and environmentally friendly methods need to be selected.
[0008] Zinc-copper-titanium alloy is an alloy material with high strength and high corrosion resistance. At present, zinc-copper-titanium alloy needs to be surface treated to improve its corrosion resistance and hydrophobicity. Therefore, improving the super hydrophobicity and corrosion resistance of zinc-copper-titanium alloy has the following prospects and advantages: First, zinc-copper-titanium alloy may be affected by corrosion and wear during use, thereby reducing its service life. By improving its super hydrophobicity and corrosion resistance, the occurrence of corrosion and wear can be reduced and its service life can be extended. Second, super hydrophobicity and corrosion resistance can improve the surface properties of zinc-copper-titanium alloy, so that it has better waterproof, anti-fouling, anti-corrosion and other properties, thereby improving its material properties. Third, zinc-copper-titanium alloy has good mechanical properties and physical properties, but its application in certain fields is limited, such as in marine environments. By improving its super hydrophobicity and corrosion resistance, its application field can be broadened and it can be used in more severe environments. Fourth, improving the super hydrophobicity and corrosion resistance of zinc-copper-titanium alloy can reduce the cost of its maintenance and replacement, thereby improving its economic benefits. Summary of the invention
[0009] The present invention aims to provide a super hydrophobic SiO2 film for the surface of zinc-copper-titanium alloy anodized film. 2 The invention relates to a preparation method and application of a hydrogel.
[0010] The core innovation of the present invention lies in that silicone oil and modifiers are used to modify the gel in the later stage of the gel preparation process to make it super hydrophobic, and the gel is roller-coated on the zinc-copper-titanium alloy anodized film to make the alloy surface film have strong corrosion resistance, thereby improving the corrosion resistance of the zinc-copper-titanium alloy anodized film.
[0011] Preparation of a novel corrosion-resistant superhydrophobic SiO2 on the surface of Zn-Cu-Ti alloy 2 The super hydrophobic SiO 2 The hydrogel film has a black coating and its surface has a porous structure and low surface energy, so it can effectively prevent the erosion of water and other corrosive media. 2 The hydrogel film can effectively improve its corrosion resistance and surface properties. The super hydrophobic film has a porous structure and low surface energy, which can effectively prevent the erosion of water and other corrosive media. It also has self-cleaning and anti-fouling functions, which can keep the surface clean and smooth. 2 The preparation method of hydrogel film is simple, low-cost, and effective, and has broad application prospects.
[0012] The preparation method and use of the present invention are divided into two parts:
[0013] The first part involves a superhydrophobic SiO2 Preparation method of hydrogel, SiO prepared by acid-base two-step method 2 The wet gel was then solvent replaced with ethanol, and the surface of the wet gel was modified with PDMS-OH and PMHS as modifiers to form a superhydrophobic SiO 2 Hydrogel;
[0014] The second part involves a superhydrophobic SiO 2 Application method of hydrogel, using super hydrophobic SiO 2 Hydrogel is used to coat and seal the pores of zinc-copper-titanium alloy anodized film.
[0015] The following is the first part of the present invention (a super hydrophobic SiO 2 Specific description of the preparation method of hydrogel):
[0016] First, the SiO2 with high hydrophobicity described in the first part of the present invention 2 Preparation method of hydrogel: including hydrolysis and condensation reaction of sodium silicate precursor to form SiO 2 hydrogel, and finally obtain superhydrophobic SiO 2 Hydrogel process.
[0017] Step (1), hydrolysis of sodium silicate:
[0018] 1. Use sodium silicate as a precursor and mix it evenly with water and silicon source in a specific ratio;
[0019] 2. Heat the mixed system at a constant temperature of 60°C to allow the system to undergo a hydrolysis reaction under acidic conditions;
[0020] 3. Hydrolysis produces silicic acid and other precursors.
[0021] Step (2), obtaining a silicon precursor (H 2 SiO colloid): After hydrolysis, a concentrated silicon precursor (H 2 SiO 3 colloid), which contains silicic acid and its related substances.
[0022] Step (3), polycondensation reaction under alkaline conditions:
[0023] 1. Under alkaline conditions, adjust the pH value of the solution by adding ammonia water;
[0024] 2. The silicon precursor undergoes a polycondensation reaction to generate Si(OH)4 monomer;
[0025] 3. Si(OH)4 monomers further condense under alkaline conditions to form a nano-network structure constructed by silicon-oxygen bonds (Si-O-Si).
[0026] 4.SiO 2 The formation of wet gel, the formation of SiO 2 The hydrogel nano-network structure forms the basis of wet gel; SiO2 wet gel has a three-dimensional network structure, but still contains liquid;
[0027] Step (4), adding pure water (H 2 O) Aging:
[0028] 1. Add pure water (H 2 O), allowing the system to age, which can be maintained for a period of time to promote the reaction;
[0029] 2. The sol is further cross-linked to form a wet gel with a three-dimensional network structure.
[0030] Step (5), solvent replacement and modification:
[0031] 1) Add ethanol (C 2 H 5 OH), and expel water;
[0032] 2) Using organic matter containing silicon to treat SiO 2 Surface modification of hydrogels;
[0033] The modifier used for surface modification is hydroxy silicone oil or hydrogen silicone oil;
[0034] The modifier used for surface modification is PDMS-OH or PMHS;
[0035] Step (6), drying to prepare SiO 2 Hydrogel:
[0036] 1. After the wet gel is formed, it is dried to remove the liquid in the pores of the wet gel, and finally the SiO2 hydrogel is obtained.
[0037] 2. Prevent the capillary force from destroying the gel network skeleton during room temperature drying.
[0038] Second, the highly hydrophobic SiO 2 Specific steps of the hydrogel preparation method:
[0039] S1, diluted sodium silicate (Na 2 SiO 3 ): Dilute 35% industrial grade sodium silicate solution.
[0040] S2, acid-base two-step method to convert the sol system into SiO 2 Hydrogel;
[0041] a. Acidification reaction: In the presence of hydrochloric acid (HCl), the pH value of the sol system is adjusted to 2-3 to create acidic conditions. In an acidic environment, silicate ions (SiO) can combine with gas ions (H+).
[0042] Formation of silicic acid (H 2 SiO 3 ), the reaction equation is:
[0043] Na 2 SiO 3 +2HCl→2NaCl+H 2 SiO 3
[0044] b. Alkalinization reaction: In ammonia (NH 3 H 2 O) and adjust the pH to 6 to create alkaline conditions. In an alkaline environment, silicic acid (HSiO) can react with ammonia molecules (NH 3 ) to form a silicon-releasing group (Si(OH) 4 ), the reaction equation is:
[0045] Na 2 SiO 3 +2HCl→2NaCl+H 2 SiO 3
[0046] c. Target product: sol-gel. The structural formula of sol-gel is:
[0047]
[0048] S3, standing gel formation:
[0049] a. Allow the sol system to stand: Allow the sol system after acid-base adjustment to stand without stirring or other mechanical intervention.
[0050] b. Producing preliminary gel: As the system stands still, the hydrolysis and polymerization reactions in the system lead to the formation of gel. The preliminary gel does not change the chemical structure of the pre-product (sol-gel). Therefore, the structural formula of the preliminary gel is:
[0051]
[0052] S4, add pure water (H 2 O) Aging:
[0053] a. Add pure water (H 2 O), allowing the system to age, which can be maintained for a period of time to promote the reaction;
[0054] b. The sol is further cross-linked to form a wet gel with a three-dimensional network structure.
[0055] S5, solvent replacement:
[0056] a. Add ethanol to the sol system (C 2 H 5 OH).
[0057] b. Drain water (H 2 O): Perform drainage operation to remove water from the system.
[0058] S6, Surface modification: Utilizing organic matter containing silicon to modify SiO 2 Surface modification of hydrogels.
[0059] a. Prepare SiO 2 Hydrogel;
[0060] b. Selecting a surface modifier (hydrogen silicone oil and hydroxy silicone oil) as a surface modifier;
[0061] c. Performing surface modification reaction;
[0062] (a) The structural formula of hydrogen-containing silicone oil is
[0063]
[0064] (1) Structural formula of hydrogenated silicone oil
[0065] The surface modification reaction formula of hydrogenated silicone oil is:
[0066] Si(OH) 4 +R-SiH 3 →Si-O-SiR+H 2 O
[0067] Wherein, R is an organic group;
[0068] (b) The structural formula of hydroxy silicone oil is:
[0069]
[0070] (2) Hydroxy silicone oil structure
[0071] The surface modification reaction formula of hydroxy silicone oil is:
[0072] Si(OH) 4 +R'-Si(OH) 3 →Si-O-SiR'+H 2 O
[0073] Wherein, R' is an organic group;
[0074] d.SiO 2 Chemical modification methods and modification solutions for hydrogel surface modification: PMHS modification and PDMS-OH, two similar silane alkyl compounds
[0075] PMHS (polymethylsilane) modification, through the active silicon-hydrogen bond (Si-H bond) on the PMHS molecular chain and SiO 2 The hydroxyl-OH groups on the surface of the hydrogel react to form a covalently bonded grafted structure;
[0076] The active silicon-hydrogen bond (Si-H bond) on the PMHS (polydimethylsilane) molecular chain and SiO 2 The hydroxyl groups (-OH groups) on the surface of the hydrogel react, and the chemical formula is expressed as:
[0077] PMHS+SiO 2 →PMHS-SiO 2
[0078] In this reaction, the Si-H bonds in PMHS react with SiO 2 The -0H groups in the hydrogel undergo condensation reaction to form PMHS-SiO 2 This reaction of compounds usually requires appropriate catalysts or reaction conditions to promote the reaction;
[0079] The methyl group (-CH3) on the PMHS molecular chain is hydrophobic, thus achieving 2 Hydrophobic modification of the hydrogel surface. The following is the reaction process:
[0080] SiO 2 -OH+PMHS-SiHx→SiO 2 -SiHx+PMHS-OH
[0081] Among them, SiO 2 -0H represents SiO 2 The hydroxyl groups on the hydrogel surface, PMHS-SH, represent the silicon-hydrogen groups on the PMHS molecular chain, SiO 2 -SiH represents grafted on SiO 2 The silicon-hydrogen groups on the hydrogel surface, PMHS-OH represents the hydroxyl groups grafted on the PMHS molecular chain;
[0082] The grafting process forms a strong covalent bond covering the SiO 2 The hydrophilic hydroxyl groups on the surface of the hydrogel give it hydrophobic properties;
[0083] The structural formula of PMHS (polydimethylsilane) modification is:
[0084]
[0085] (3) PMHS (polydimethylsilane) modified structure
[0086] In this reaction, PMHS, as an organic silicon compound containing active Si-H bonds, can form covalent bonds by grafting with -OH groups, thereby firmly covering the SiO 2 On the hydrogel surface;
[0087] The coating can cover the hydrophilic -OH groups, making SiO 2 Hydrogels have hydrophobic properties;
[0088] The PDMS-OH (hydroxy polydimethylsiloxane) in (d) can undergo a hydrolysis reaction to generate small molecule substances;
[0089] The PDMS-OH (hydroxy polydimethylsiloxane) in (d) can generate small molecules during the hydrolysis process. The two hydroxyl groups (-OH) on the surface of the hydrolysis product can react with SiO 2 Hydroxyl-OH reaction on the hydrogel surface realizes the 2 Grafting on hydrogel surface;
[0090] In (d), the reaction process of PDMS-OH (hydroxy polydimethylsiloxane):
[0091] SiO 2 -OH+PDMS-OH→SiO 2 -O-PDMS-OH+H 2 O
[0092] Among them, SiO 2 -0H represents SiO 2 Hydroxyl groups on the hydrogel surface, PDMS-OH represents PDMS-OH molecules, SiO 2 -0-PDMS-OH represents the grafted 2 PDMS-OH on the hydrogel surface;
[0093] This reaction process will form a covalent bond, so that the PDMS-OH molecular chain is grafted on the SiO 2 hydrogel surface;
[0094] Due to the small molecular structure of the hydrolyzate, its steric hindrance is small, which is conducive to the grafting reaction, thereby achieving a higher grafting rate; such a grafting reaction can make SiO 2 The hydrogel changes from hydrophilic to hydrophobic;
[0095] The structural formula of PDMS-OH (hydroxy polydimethylsiloxane) is:
[0096]
[0097] (4) Structural formula of PDMS-OH (hydroxy polydimethylsiloxane)
[0098] d. The product of the modification reaction is grafted onto the surface hydroxyl -OH.
[0099] Third, the SiO2 with high hydrophobicity described in the first part of the present invention 2 Design concept and detailed description of the hydrogel preparation method:
[0100] The S1 diluted sodium silicate (Na 2 SiO 3 ) in the presence of sodium silicate (Na 2 SiO 3 ) is diluted in order to adjust the concentration of the solution during the synthesis of sodium silicate to meet the requirements of the experiment and optimize the subsequent preparation steps;
[0101] Preferably, water glass is diluted with deionized water (sodium silicate: deionized water), and stirred at 60° C. for 5 minutes to make it uniformly dispersed;
[0102] Preferably, the concentration control, diluting the sodium silicate solution can help control the concentration of the reaction system; the concentration control can ensure that the solution concentration obtains the desired product or properties during the formation or reaction process;
[0103] Preferably, the reaction conditions are optimized, and the conditions of the subsequent reaction steps can be optimized by diluting the sodium silicate; the reaction conditions are optimized, and the subsequent experimental steps may have specific requirements for the concentration of the solution, so as to achieve more ideal experimental results;
[0104] The S2 acid-base two-step method converts the sol system into an acidification reaction in the gel (a). Under acidic conditions, the hydrogen ions (H+) in the hydrochloric acid combine with the negative ions (such as silicate ions) in the sol system to form an unstable compound (silicic acid (H+)). 2 SiO 3 ));
[0105] The S2 acid-base two-step method converts the sol system into an acidification reaction (a) in the gel, which can reduce the stability of the sol system, causing precursors such as sodium silicate to undergo hydrolysis and polymerization reactions to form a precipitate, and gradually form the basic structure of the gel;
[0106] The S2 acid-base two-step method converts the sol system into a gel in an alkalization reaction (b). Under alkaline conditions, silicate (H 2 SiO 3 ) and hydroxide ions (OH - ) to form a stable silicate ion (SiO3 2- );
[0107] The ammonia (NH 3 H 2 O) is an alkaline substance, which plays a role in the alkalization process by converting silicic acid (HSO) into silanol (SiOH));
[0108] The S2 acid-base two-step method converts the sol system into a gel in the alkalinization reaction (b), and the hydroxide ions (OH - ) and the hydrogen ions (H + ) combine to form silanol groups;
[0109] The S2 acid-base two-step method converts the sol system into an alkalization reaction (b) in the gel, which can adjust the acid-base balance of the system so that the hydrolysis and polymerization reactions continue under alkaline conditions, which helps to form a gel structure;
[0110] The S2 acid-base two-step method converts the sol system into the target product (c) in the gel, and the sol system is converted into a sol-gel by the acid-base two-step method;
[0111] The sol-gel is a semi-solid colloidal system (in a semi-solidified transparent state), in which colloidal particles form a three-dimensional network structure through chemical or physical interactions;
[0112] The S2 acid-base two-step method converts the sol system into a hydrogel. Through acidification and alkalization reactions, hydrochloric acid and ammonia water jointly convert sodium silicate into silanol groups, thereby achieving the preparation of sodium silicate.
[0113] The S2 acid-base two-step method converts the sol system into a gel acid-base two-step method, and then heats the system at a constant temperature of 60°C to hydrolyze the system under acidic conditions. The control of reaction temperature and time is very important for the reaction process and the quality of the target product. The details are as follows:
[0114] The S2 acid-base two-step method converts the sol system into a gel. In the acid-base two-step method, the reaction temperature is controlled as follows:
[0115] For the acidification reaction (step a), it is carried out at room temperature, but the specific temperature depends on the reagents and reaction system used; for the alkalization reaction (step b), the temperature can be controlled at room temperature or slightly heated to promote the reaction;
[0116] The S2 acid-base two-step method converts the sol system into a gel. In the acid-base two-step method, the reaction time is controlled as follows:
[0117] For the acidification reaction (step a), the reaction time is usually short, generally between a few minutes and tens of minutes; under acidic conditions, the reaction rate is fast, and too long a reaction time may lead to the occurrence of side reactions;
[0118] Preferably, the reaction time is controlled to be 2-24 hours for static hydrolysis;
[0119] For the alkalization reaction (step b), the reaction time can be slightly longer, generally between tens of minutes and several hours; under alkaline conditions, the reaction rate is relatively slow, and sufficient time is required to complete the hydrolysis and polymerization reactions.
[0120] The stationary sol system (a) formed by the S3 stationary gel can allow the hydrolysis reaction and polymerization reaction in the sol to proceed spontaneously to form a preliminary gel structure.
[0121] The S3 is allowed to stand to form a preliminary gel (b), which is a material with a certain consistency and network structure. The preliminary gel is not yet stable and strong enough, but has the basic structure to form a more solid gel.
[0122] The standing waiting time for the formation of the S3 standing gel is also called the gel time. The gel time is characterized as follows: starting from the addition of ammonia water or hydrochloric acid, the solution gradually cross-links, and ending when the sol surface does not flow after the sol system is tilted 45 degrees. This period of time is the gel time;
[0123] In the formation of S3 standing gel, the standing waiting time (gel time) means starting from the adjustment of acid-base conditions, the sol system is gradually cross-linked by standing waiting, and finally SiO 2 Hydrogel;
[0124] The end point of the gel time can be determined by certain experimental means, such as tilting the sol system at 45° and observing whether the sol liquid surface flows; when the sol liquid surface no longer flows, the gel time ends.
[0125] The optimal gel time may be stabilized at about half an hour after the preparation process matures.
[0126] In the step S4, water is added to the gel system for aging. The aging process can provide sufficient time for the reaction to proceed more fully to obtain the desired product.
[0127] In the step of adding water to the gel system for aging in S4, pure water (a) is added to the sol system. On the one hand, the concentration of the sol system can be adjusted by the addition of pure water, which helps to form a more uniform and stable gel; on the other hand, the addition of pure water will cause some hydrolysis and polymerization reactions to continue, further promoting the formation of a gel structure;
[0128] In the step S4, pure water is added to the gel system for aging (b), and after the pure water is added, the sol system is kept for a period of time so that the chemical reaction reaches a more sufficient degree, thereby forming a more stable and firm gel structure;
[0129] The aging time is controlled within 12-42 hours, which is sufficient time to ensure the desired reaction occurs, thereby obtaining the ideal SiO 2 Hydrogel properties;
[0130] In the step S4, water is added to the gel system for aging, and the sol is further cross-linked to form a wet gel. On the basis of aging, the structure of the gel is further stabilized through a further cross-linking reaction, and a wet gel having a three-dimensional network structure is formed;
[0131] The wet gel has a large number of pore structures, which may affect the final SiO 2 Properties of hydrogels;
[0132] In the step S4, water is added to the gel system for aging, and the operation in the whole process affects the evolution of the structure and properties of the gel system.
[0133] In the S5 solvent replacement, adding ethanol can replace the water in the system;
[0134] The addition of ethanol in the S5 solvent replacement helps to change the solvent properties of the system to obtain better coating performance;
[0135] In the solvent replacement of S5, ethanol (a) is added to the sol system. On the one hand, ethanol, as an organic solvent, has a smaller polarity than water, which helps to change the polarity of the system, affect the reaction and the properties of the product, and achieve a change in the properties of the solvent; on the other hand, ethanol helps to dissolve or disperse various components in the system, improves solubility, and helps to better react or perform subsequent treatments.
[0136] The S5 solvent substitution involves expelling water from the sol system (b). On the one hand, by adding ethanol, water is replaced out of the system, thereby changing the solvent environment of the reaction system and achieving solvent substitution. On the other hand, the presence of water may be detrimental to the reaction. Therefore, by expelling water, the reaction direction can be controlled and hydrolysis can be prevented.
[0137] In the surface modification of S6, for SiO 2 For hydrogel, the surface modification method is to use organic matter containing silicon, such as hydrogen silicone oil and hydroxy silicone oil, to carry out grafting reaction;
[0138] In the surface modification of S6, SiO 2The main purposes of surface modification of hydrogels include changing their hydrophilicity / hydrophobicity, increasing chemical reactivity, and improving stability;
[0139] In the surface modification of S6, SiO 2 The specific implementation steps (ae) of the hydrogel surface modification include: a. preparing SiO 2 hydrogel (i.e. the product obtained in the previous step); b. selecting a surface modifier (hydrogen silicone oil and hydroxy silicone oil) as a surface modifier; c. performing a surface modification reaction; d. SiO 2 Chemical modification methods and modification solutions for surface modification of hydrogels: PMHS modification and PDMS-OH, two similar silane alkyl compounds; e. The product of the modification reaction is grafted onto the surface hydroxyl -OH;
[0140] The SiO2 that needs to be prepared in (a) of the S6 surface modification 2 The hydrogel is SiO obtained by the previous five steps (S1 to S5). 2 Hydrogel, ensuring it has good pore structure and chemical activity;
[0141] The surface modifier (hydrogen silicone oil and hydroxy silicone oil) in the surface modification of S6 (b) contains a silicon-oxygen bond (Si-O-Si bond) and has a 2 the potential for reactions to occur on the hydrogel surface;
[0142] In the surface modification of S6 (c), the surface modifier (a) is a hydrogen silicone oil structural formula and (b) is a hydroxy silicone oil structural formula, and the structural formula contains a silicon-oxygen bond (Si-O-Si bond);
[0143] The silicon-oxygen bonds in (c) of the S6 surface modification can be bonded to SiO 2 The -OH groups on the hydrogel surface undergo condensation reactions;
[0144] The silicon-oxygen bond in (c) of the S6 surface modification is easily hydrolyzed under acid-base conditions to produce silicon hydroxyl groups (Si(OH) 4 );
[0145] The silanol group in (c) of the S6 surface modification can react with SiO 2 The hydroxyl-OH groups on the hydrogel surface condense, thereby fixing the surface modifier on the hydrogel surface;
[0146] The structural formula of the hydrogenated silicone oil in (c) in the surface modification of S6 is:
[0147]
[0148] (1) Structural formula of hydrogenated silicone oil
[0149] The surface modification reaction formula of the hydrogenated silicone oil in (c) of the S6 surface modification is:
[0150] Si(OH) 4 +R-SiH 3 →Si-O-SiR+H 2 O
[0151] Wherein, R is an organic group;
[0152] The structural formula of the hydrogen-containing silicone oil in (1) in (c) of the S6 surface modification comprises Si-H bonds, wherein the silicon atom is connected to the hydrogen atom;
[0153] The structure of the hydrogenated silicone oil in (c) of the surface modification of S6 can provide active silicon-H bonds for bonding with SiO 2 The -OH groups on the hydrogel surface react;
[0154] The structural formula of the hydroxy silicone oil in (c) in the S6 surface modification is:
[0155]
[0156] (2) Hydroxy silicone oil structure
[0157] The surface modification reaction formula of the hydroxy silicone oil in (c) in the S6 surface modification is:
[0158] Si(OH) 4 +R'-Si(OH) 3 →Si-O-SiR'+H 2 O
[0159] Wherein, R' is an organic group;
[0160] The structural formula of the hydroxy silicone oil (2) in (c) of the S6 surface modification comprises a Si-O-Si bond and a hydroxyl group (-OH);
[0161] The hydroxyl group in (c) of the S6 surface modification is easily hydrolyzed under acidic and alkaline conditions to produce silanol Si(OH)4. 2 The hydroxyl-OH groups on the surface of the hydrogel undergo condensation reaction, thereby achieving surface modification;
[0162] In the surface modification of S6 (d), two chemical modification methods and modification solutions were used for surface modification: PMHS modification and PDMS-OH, two similar silane alkyl compounds;
[0163] PMHS and PDMS-OH in the surface modification of S6 (d) can be the same substance, or have similar structures and properties, and can be used for SiO 2 Surface modification of hydrogels to render them hydrophobic;
[0164] In the surface modification of S6 (d), PMHS and PDMS-OH have similar roles in the modification, both of which are through the interaction with SiO 2 The -OH groups on the hydrogel surface react to introduce hydrophobic groups, thereby changing the SiO 2 Properties of the hydrogel surface;
[0165] In the surface modification of S6 (d), PMHS and PDMS-OH both contain silicon-oxygen bonds, but PMHS mainly reacts through silicon-hydrogen bonds, while PDMS-OH participates in the reaction through the hydroxyl groups produced by hydrolysis;
[0166] In the surface modification of S6 (d), PMHS and PDMS-OH are used as chemical modification solutions to introduce hydrophobic groups to change the SiO 2 The hydrophilicity of the hydrogel surface prevents water absorption and moisture, thus maintaining the performance of the hydrogel;
[0167] In the surface modification of S6 (d), PMHS (polymethylsilane) is modified by the active silicon-hydrogen bond (Si-H bond) on the PMHS molecular chain and SiO 2 The hydroxyl-OH groups on the surface of the hydrogel react to form a covalently bonded grafted structure;
[0168] In the surface modification of S6 (d), the active silicon-hydrogen bonds (Si-H bonds) on the PMHS (polydimethylsilane) molecular chain and SiO 2 The hydroxyl groups (-OH groups) on the surface of the hydrogel react, and the chemical formula is expressed as:
[0169] PMHS+SiO 2 →PMHS-SiO 2
[0170] In this reaction, the Si-H bonds in PMHS react with SiO 2 The -0H groups in the 2 Compounds, this reaction usually requires appropriate catalysts or reaction conditions to promote the reaction;
[0171] The methyl group (-CH3) on the PMHS molecular chain is hydrophobic, thereby achieving 2 Hydrophobic modification of the hydrogel surface. The following is the reaction process:
[0172] SiO2 -OH+PMHS-SiHx→SiO 2 -SiHx+PMHS-OH
[0173] Among them, SiO2-0H represents SiO 2 The hydroxyl groups on the hydrogel surface, PMHS-SH, represent the silicon-hydrogen groups on the PMHS molecular chain, SiO2-SiH represents the silicon-hydrogen groups grafted on the SiO2 surface, and PMHS-OH represents the hydroxyl groups grafted on the PMHS molecular chain;
[0174] The grafting process forms a strong covalent bond covering the SiO 2 The hydrophilic hydroxyl groups on the surface of the hydrogel give it hydrophobic properties;
[0175] The structural formula of PMHS (polydimethylsilane) modification is:
[0176]
[0177] (3) PMHS (polydimethylsilane) modified structure
[0178] In this reaction, PMHS, as an organic silicon compound containing active Si-H bonds, can form covalent bonds by grafting with -OH groups, thereby firmly covering the SiO 2 On the hydrogel surface;
[0179] The PMHS covering can cover the hydrophilic -OH groups to make SiO 2 Hydrogels have hydrophobic properties;
[0180] In the surface modification of S6 (d), PDMS-OH is hydroxylated polydimethylsiloxane, and its molecular structure includes silicon-oxygen bonds and groups (-OH). The chemical formula of DMS-OH (hydroxylated polydimethylsiloxane) is as follows:
[0181] PDMS-OH:(CH 3 SiO 1.5 ) n -(CH 2 CH 2 SiO 1.5 ) m -OH
[0182] Among them, n and m are the number of repeating units in the polymer chain, (CH3SiO1.5) and (CH2CH2SiO1.5) represent polydimethylsiloxane and polypropylene oxide units respectively; this structure contains hydroxyl groups, which can generate small molecules when hydrolyzed, and the generated hydroxyl groups can react with SiO 2 The hydroxyl-OH reaction on the hydrogel surface realizes the2 Modification of hydrogel surface;
[0183] In the surface modification of S6 (d), PDMS-OH (hydroxy polydimethylsiloxane) can undergo hydrolysis reaction to generate small molecule substances;
[0184] In the surface modification of S6 (d), PDMS-OH (hydroxy polydimethylsiloxane) can generate small molecules during the hydrolysis process. The two hydroxyl groups (-OH) on the surface of the hydrolysis product can react with SiO 2 Hydroxyl-OH reaction on the hydrogel surface realizes the 2 Grafting on the surface of hydrogel film;
[0185] In the surface modification of S6 (d), the reaction process of PDMS-OH (hydroxy polydimethylsiloxane) is:
[0186] SiO 2 -OH+PDMS-OH→SiO 2 -O-PDMS-OH+H 2 O
[0187] Among them, SiO2-0H represents SiO 2 The release groups on the surface of the hydrogel, PDMS-OH represents PDMS-OH molecules, SiO2-0-PDMS-OH represents the grafted 2 PDMS-OH on the hydrogel surface;
[0188] This reaction process will form a covalent bond, so that the PDMS-OH molecular chain is grafted on the SiO 2 Hydrogel film surface;
[0189] Due to the small molecular structure of the hydrolyzate, its steric hindrance is small, which is conducive to the grafting reaction, thereby achieving a higher grafting rate; such a grafting reaction can make SiO 2 The hydrogel changes from hydrophilic to hydrophobic;
[0190] The structural formula of PDMS-OH (hydroxy polydimethylsiloxane) is:
[0191]
[0192] (4) Structural formula of PDMS-OH (hydroxy polydimethylsiloxane)
[0193] In the S6 surface modification (d), during the hydrolysis of PDMS-OH (hydroxyl-terminated polydimethylsiloxane), the Si-O-Si bond in the PDMS-OH molecule will break, generating a small molecule substance containing two -OH groups;
[0194] The steric hindrance of the small molecule hydrolysate is small, which means that the molecular structure of the small molecule hydrolysate is relatively small, and there are no large groups or molecular chains to hinder the reaction;
[0195] The small molecule hydrolysis product and SiO 2 The grafting rate of -OH reaction on the hydrogel surface is high;
[0196] In the modification reaction of PDMS-OH (hydroxyl-terminated polydimethylsiloxane), the two -OH groups of the small molecule hydrolyzate can react with SiO 2 The -OH groups on the hydrogel surface undergo condensation reactions to form covalent bonds;
[0197] The formation of covalent bonds in the modification reaction of PDMS-OH (hydroxyl-terminated polydimethylsiloxane) can make SiO 2 The surface properties of the hydrogel change from hydrophilic to hydrophobic;
[0198] In the surface modification of S6 (d), SiO 2 The PMHS modification process of hydrogel is to use the active Si-H bond on the molecular chain to react with the -OH group to form a covalent bond, thereby covering the SiO 2 hydrogel surface;
[0199] In the S6 surface modification (d), PMHS modification process:
[0200] Active Si-H bonds react with -OH groups, and the active silicon-hydrogen bonds (Si-H bonds) on the PMHS (polydimethylsilane) molecular chain react with SiO 2 The hydroxyl groups (-OH groups) on the surface of the hydrogel react;
[0201] The active Si-H bond reacts with the -OH group, and the silicon-hydrogen bond condenses with the hydroxyl group to form a covalent bond;
[0202] The product of the modification reaction in (e) of the S6 surface modification is silanol, which can react with SiO 2 The hydroxyl -OH on the surface of the hydrogel undergoes a condensation reaction, thereby grafting the organosilicon compound onto the SiO 2 hydrogel surface;
[0203] In the surface modification of S6 (e), after the surface modification reaction, the generated Si-O-Si bonds firmly connect the surface modifier to the SiO 2 The hydrogel surface forms a grafting effect;
[0204] The grafting effect in the surface modification of S6 (e) helps to improve the SiO 2Stabilize the hydrogel, reduce its water absorption, and change its surface properties;
[0205] In the surface modification of S6 (e), SiO 2 The -OH groups on the surface of the hydrogel have an affinity for water, making SiO 2 Hydrogels easily absorb water and moisture;
[0206] The -OH groups in the surface modification of S6 (e) are prone to dehydration and condensation during the drying process, resulting in SiO 2 The pores of the hydrogel shrink and the structure collapses, thus affecting its performance.
[0207] Fourth, the highly hydrophobic SiO 2 Target product obtained by hydrogel preparation method: a super-hydrophobic SiO2 for the surface of zinc-copper-titanium alloy anodized film 2 Hydrogel;
[0208] Furthermore, the super hydrophobic SiO 2 The hydrogel was prepared by an acid-base two-step method, followed by solvent replacement with ethanol, and modified with PMHS (polydimethylsiloxane) and PDMS-OH (hydroxypolydimethylsiloxane), and possessed excellent superhydrophobicity and corrosion resistance.
[0209] Preferably, the super hydrophobic SiO 2 The hydrogel surface changes from hydrophilic to hydrophobic;
[0210] Preferably, the super-hydrophobic silica hydrogel is modified by PMHS (polydimethylsilane) and PDMS-OH (hydroxy polydimethylsiloxane), and the formation of covalent bonds improves weather resistance;
[0211] Furthermore, the super-hydrophobic silica hydrogel can improve the crack resistance of the alloy surface, making it more wear-resistant and durable;
[0212] Preferably, the super hydrophobic SiO 2 The hydrogel was modified with PMHS (polydimethylsilane) and PDMS-OH to reduce the steric hindrance of the hydrolysis product, improve the grafting process, and increase the grafting rate to XX%.
[0213] Preferably, the super hydrophobic SiO 2 The first application of hydrogel is to coat and seal the surface of zinc-copper-titanium alloy anodized film, thereby forming a corrosion-resistant superhydrophobic SiO 2 Hydrogel film (black coating) improves the overall hydrophobicity and corrosion resistance of zinc-copper-titanium alloy.
[0214] The following is the second part of the present invention (a super hydrophobic SiO2 Specific description of the use method of hydrogel coating and sealing the pores of zinc-copper-titanium alloy anodic oxide film:
[0215] First, the highly hydrophobic SiO 2 Application method of hydrogel coating and sealing of zinc-copper-titanium alloy anodic oxide film:
[0216] The SiO 2 The coating method of the hydrogel is to use a roller brush to roll the zinc-copper-titanium alloy anodized film 1-3 times after the gel modification is completed. After each coating, it is placed in a drying oven for gradient drying;
[0217] The coating tool in the laboratory is a 2-inch short-haired roller brush, the size of which is 25 cm in length and 5 cm in width;
[0218] The coating tool is usually a rubber twin roller of corresponding size in industrial preparation;
[0219] The rubber double rollers are usually made of natural rubber or synthetic rubber;
[0220] The size of the rubber double roller should match the size of the material being processed. Selecting a suitable rubber double roller according to the size of the zinc-copper-titanium alloy material can improve the uniformity and efficiency of coating.
[0221] The rubber double rollers should be smooth and flawless to improve the coating quality and effect.
[0222] The rubber double rollers should be selected to have appropriate elasticity to ensure that the coated hydrogel has good adhesion and uniformity.
[0223] The hardness of the rubber double roller should match the hardness of the material being processed to ensure the coating effect and quality;
[0224] The SiO 2 The coating dosage of the hydrogel is about 1g, so that the gel remaining on the surface of the oxide film is small and uniform;
[0225] The SiO 2 The number of roller coating of the hydrogel is controlled to be 1-3 times, and the interval between each coating is generally 10 minutes, so that the gel and the substrate are fully combined; preferably, the roller coating is selected twice, with an interval of 10 minutes in between;
[0226] The SiO 2 After the hydrogel coating is completed, gradient drying is performed.
[0227] Second, the super hydrophobic SiO 2The specific steps of the method for using hydrogel to seal the pores of zinc-copper-titanium alloy anodic oxide film are as follows:
[0228] Step (1), pre-treatment of the anodic oxide film of the zinc-copper-titanium alloy: the zinc-copper-titanium alloy is subjected to casting, cutting, electrolytic activation, and substrate cleaning, thereby forming an anodic oxide film on the surface of the zinc-copper-titanium alloy;
[0229] Step (2), prepare the prepared SiO 2 hydrogels, inspecting and ensuring they have the appropriate properties;
[0230] Step (3), using the prepared SiO 2 The hydrogel is coated and sealed on the surface of the zinc-copper-titanium alloy anodic oxide film to ensure that the surface of the zinc-copper-titanium alloy anodic oxide film is completely covered with SiO 2 hydrogel; and wait for a certain period of time to ensure that the hydrogel fully penetrates and covers the surface of the anodized film;
[0231] Step (4), drying the zinc-copper-titanium alloy anodized film sample coated with the hydrogel to remove excess solvent and water, so that the hydrogel forms a uniform black coating on the surface (super-hydrophobic SiO 2 Gel film);
[0232] Step (5), checking the uniformity and integrity of the coating to ensure the sealing effect;
[0233] Step (6), in order to ensure the uniform effect of the zinc-copper-titanium alloy anodized film coating, the coating step can be repeated to adjust the thickness of the coating;
[0234] Step (7), super hydrophobic SiO 2 The gel film was dried in a gradient manner.
[0235] Third, the super hydrophobic SiO 2 Design concept and detailed description of the use method of hydrogel coating and sealing the pores of zinc-copper-titanium alloy anodic oxide film:
[0236] The zinc-copper-titanium alloy obtained after the anodizing treatment has completed the pre-treatment of the oxide film, and the pre-treatment is the electrolytic activation treatment of the zinc-copper-titanium alloy anodizing, including: placing the zinc-copper-titanium alloy in an electrolytic activation solution, using the zinc-copper-titanium alloy as an anode, a lead plate as a cathode, applying direct current, and forming an electrolytic cell with NaOH as an electrolyte; then taking out the zinc-copper-titanium alloy and washing it with water;
[0237] Preferably, in terms of mass percentage, the raw material ratio of the zinc-copper-titanium alloy is 89.5% zinc (Zn), 1% copper (Cu), and 0.5% titanium (Ti);
[0238] The anodizing solution comprises: 1L ultrapure water mixed with 10g NaOH in volume percentage;
[0239] The current used for the anodic oxidation electrolytic activation treatment is 50mA;
[0240] The oxidation temperature for the anodic oxidation electrolytic activation treatment is 35°C;
[0241] The oxidation time for the anodic oxidation electrolytic activation treatment is 30 minutes;
[0242] In the electrolytic cell, an oxidation reaction occurs at the anode and a reduction reaction occurs at the cathode;
[0243] The anode (zinc-copper-alloy) loses electrons, undergoes oxidation reaction, and forms metal ions (Zn2Cu2+Ti4+) that enter the electrolyte;
[0244] The cathode (lead plate) will gain electrons and undergo a reduction reaction to form hydrogen (H 2 );
[0245] The reaction formula of the electrolytic cell is expressed as:
[0246] Anode: 2OH - -2e - =[O]+H 2 O, Zn+[O]=ZnO
[0247] Cathode: 2H 2 O+2e - =H 2 ↑+2OH -
[0248] Overall reaction: Zn+H 2 O=H 2 ↑+ZnO
[0249] Therefore, the hydrogel is a hydrogel prepared and modified by the first part of the present invention, and the characteristic slightly modified hydrogel can improve the adhesion and uniformity of the gel, ensuring that the coating can be firmly attached to the surface of the zinc-copper-titanium alloy oxide film;
[0250] There are two types of tools for coating hydrogel on the surface of zinc-copper-titanium alloy oxide film, namely, a 2-inch short-hair roller brush and a rubber double roller;
[0251] The coating tool is a 2-inch short-hair roller brush, the size of which is 5 to 10 cm in diameter and 8 cm in width.
[0252] The coating tool is usually a rubber twin roller of corresponding size in industrial preparation;
[0253] The rubber double rollers are usually made of natural rubber or synthetic rubber;
[0254] The size of the rubber double roller should match the size of the material being processed. Selecting a suitable rubber double roller according to the size of the zinc-copper-titanium alloy material can improve the uniformity and efficiency of coating.
[0255] The rubber double rollers should be smooth and flawless to improve the coating quality and effect.
[0256] The rubber double rollers should be selected to have appropriate elasticity to ensure that the coated hydrogel has good adhesion and uniformity.
[0257] The hardness of the rubber double roller should match the hardness of the material being processed to ensure the coating effect and quality;
[0258] SiO 2 The coating dosage of the hydrogel is about 1g, and the gel attached to the surface can be fine-tuned according to the actual effect;
[0259] The SiO 2 The coating interval of the hydrogel is 10 minutes between each coating to allow the hydrogel to fully combine with the substrate, which helps to ensure the uniformity and adhesion of the coating layer;
[0260] SiO 2 The number of times the hydrogel is applied should be controlled within the range of 1-3 times;
[0261] Preferably, SiO 2 The hydrogel was coated twice with a 10-min interval in between to ensure that the gel fully penetrated and bonded to the oxide film;
[0262] Preferably, SiO 2 After the hydrogel coating is completed, gradient drying is performed.
[0263] SiO 2 After the hydrogel coating is completed, gradient drying should be performed;
[0264] The gradient drying is performed to avoid uneven drying and shrinkage that may be caused by rapid temperature changes. Gradually increasing the temperature can ensure that the gel layer remains uniform during the drying process;
[0265] The gradient drying comprises: applying super-hydrophobic SiO 2 The hydrogel film is dried in a drying oven;
[0266] The drying process is carried out in a drying oven by gradient temperature increase and normal pressure drying to obtain SiO 2 Gel film;
[0267] Preferably, the drying process is performed 4 times;
[0268] Preferably, the temperatures of the four drying treatments are 30° C., 60° C., 90° C., and 120° C. respectively;
[0269] Preferably, the time of the four drying treatments is controlled to be 0.5 hours each time according to the material ratio;
[0270] Preferably, after the four drying treatments, the SiO 2 The hydrogel film needs to be taken out of the drying oven and allowed to stand at room temperature after drying;
[0271] Preferably, after the four drying treatments, the SiO 2 The hydrogel film needs to be subjected to electrochemical and other tests, and the test results show that SiO 2 The static contact angle of the hydrogel film is not less than 120°.
[0272] Fourth, the super hydrophobic SiO 2 Application of hydrogel to seal pores of zinc-copper-titanium alloy anodic oxide film Target product: A novel corrosion-resistant superhydrophobic SiO2 film on the surface of zinc-copper-titanium alloy anodic oxide 2 Hydrogel film (black coating or white coating);
[0273] Furthermore, the SiO 2 The hydrogel coating (black coating or white coating) has the characteristic of being covalently bonded to the zinc-copper-titanium alloy substrate, forming a strong chemical bond with the substrate, and the hydrophobic property extends to the zinc-copper-titanium alloy anodized film, providing hydrophobicity to the entire alloy surface;
[0274] Furthermore, the formation of covalent bonds and the addition of hydrophobic properties make SiO 2 The hydrogel film (black coating or white coating) forms a strong connection with the substrate and the anodic oxide film, improving the overall corrosion resistance of the zinc-copper-titanium alloy;
[0275] Furthermore, the roller coating process ensures that the SiO 2 The hydrogel coating can be evenly attached to the outside of the anodized layer to form a uniform hydrophobic coating, which improves the SiO 2 The effect and consistency of hydrogel films;
[0276] Further SiO 2 The super-hydrophobicity of the hydrogel film (black coating or white coating) makes the surface of zinc-copper-titanium alloy have the property of repelling water molecules, which can reduce the adsorption and corrosion of liquids in waterproof and anti-corrosion occasions;
[0277] Furthermore, SiO 2 The hydrogel film (black coating or white coating) shares hydrophobicity with the zinc-copper-titanium alloy anodized film, and the entire zinc-copper-titanium alloy surface has consistent properties, thereby increasing the integrity of the zinc-copper-titanium alloy surface.
[0278] Beneficial effects of the present invention:
[0279] First, the super-hydrophobic SiO 2 Hydrogels, solvent replacement and surface modification produce excellent superhydrophobicity and corrosion resistance effects:
[0280] First, the effect of PMHS modification:
[0281] 1. Formation of covalent bonds. Due to the condensation reaction of active Si-H bonds and -OH groups, strong covalent bonds are formed, which makes the PMHS molecular chain tightly covered on the SiO 2 On the surface of the hydrogel, a strong modified layer is formed;
[0282] 2. Covering hydrophilic -OH, SiO 2 The hydrogel surface originally has a large number of hydrophilic hydroxyl groups (-OH);
[0283] 3. Through the modification of PMHS, these hydrophilic -OH groups are covered, reducing the hydrophilicity of the hydrogel surface;
[0284] The PMHS modification effect brings about performance improvements:
[0285] 1. The introduction of hydrophobic properties: the -CH3 group on the PMHS molecular chain has hydrophobic properties;
[0286] 2. The hydrophobic groups are introduced into the modified SiO 2 The hydrogel surface also acquires hydrophobic properties, which can change the hydrophilic nature of the original hydrogel to make it more hydrophobic, providing superior performance in specific applications.
[0287] Second, the effect of the PDMS-OH modification:
[0288] 1. Hydrophilicity decreases, and the hydrophobic properties of PDMS-OH are transferred to SiO 2 The hydrogel surface reduces its hydrophilicity. The -CH3 group of PDMS-OH forms hydrophobicity on the surface, changing the original hydrophilicity;
[0289] 2. Covalent bonding: due to the formation of covalent bonds, the surface modification is strong and not easily washed off or worn;
[0290] 3. Small surface steric hindrance. The small molecules of PDMS-OH hydrolysis products have small steric hindrance in the reaction, which is conducive to the grafting process, thereby increasing the grafting rate;
[0291] The PDMS-OH modification effect improves performance:
[0292] 1. Improved hydrophobicity: Due to the hydrophobicity of PDMS-OH, surface modification makes SiO 2 The hydrogel changes from hydrophilic to hydrophobic, improving water resistance and moisture resistance.
[0293] 2. Heat resistance is enhanced, and the covalent bond formed by PDMS-OH modification increases the SiO 2 The heat resistance of the hydrogel improves the thermal stability of the material.
[0294] 3. Surface modification increases the surface strength and hardness of the hydrogel and improves the weather resistance of the material.
[0295] Secondly, the novel corrosion-resistant superhydrophobic SiO2 on the anodized surface of the Zn-Cu-Ti alloy 2 Corrosion resistance and hydrophobicity effects of hydrogel films (black coating or white coating):
[0296] 1.SiO 2 The gel film is covalently bonded to the zinc-copper-titanium alloy substrate, forming a strong chemical bond. This ensures a strong connection between the coating and the substrate, enhancing the overall corrosion resistance.
[0297] 2. SiO 2 The hydrophobic properties of the gel film extend to the zinc-copper-titanium alloy anodic oxide film, providing hydrophobicity to the entire alloy surface. This allows the coating to form a consistent hydrophobic protective layer on the surface, reducing liquid adsorption and corrosion.
[0298] 3. The formation of covalent bonds and the addition of hydrophobic properties ensure that SiO 2 The gel film forms a strong connection with the substrate and the anodic oxide film, which improves the overall corrosion resistance of the zinc-copper-titanium alloy.
[0299] 4. The roller coating process ensures that SiO 2 The gel coat adheres evenly to the anodized film, forming a uniform hydrophobic coating. This helps improve the effectiveness and consistency of the coating.
[0300] 5. SiO 2 The super-hydrophobic nature of the gel film (black coating or white coating) makes the surface of zinc-copper-titanium alloy have the property of repelling water molecules. This plays a key role in waterproofing and anti-corrosion occasions, reducing the adsorption and corrosion of liquids.
[0301] 6.SiO 2The gel film shares hydrophobicity with the zinc-copper-titanium alloy anodic oxide film, so that the entire zinc-copper-titanium alloy surface has consistent properties and increases the integrity of the surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0302] Figure 1 The super hydrophobic SiO2 used for the surface of the zinc-copper-titanium alloy anodic oxide film of the present invention is 2 Experimental preparation process of hydrogel;
[0303] Figure 2 The SiO 2 Orthogonal experimental design factors and levels for the preparation of hydrogel coatings (seven factors and six levels);
[0304] Figure 3 The SiO modified by silicone oil of the present invention 2 Hydrogel;
[0305] Figure 4 The SiO coating of the present invention 2 The surface of the zinc-copper-titanium anodized film sample after hydrogelation;
[0306] Figure 5 The surface of the zinc-copper-titanium anodized film sample after gradient drying of the present invention;
[0307] Figure 6 The super hydrophobic SiO2 used for the surface of the zinc-copper-titanium alloy anodic oxide film of the present invention is 2 The manufacturing process of hydrogel;
[0308] Figure 7 is the structural formula of the PMHS modification of the present invention;
[0309] Figure 8 is the structural formula of the PDMS-OH modification of the present invention;
[0310] Fig. 9 The super hydrophobic SiO 2 Comparison of polarization curves of hydrogel coatings with other parameters;
[0311] Fig.10 A data table after polarization curve fitting of the present invention;
[0312] Fig.11 It is a detailed data trend diagram after polarization curve fitting of the present invention;
[0313] Fig.12 The super hydrophobic SiO 2 Side view of the hydrogel film (cross-sectional view of a water drop on the sample surface);
[0314] Fig.13The super hydrophobic SiO 2 Film ratio table. DETAILED DESCRIPTION
[0315] The purpose of the present invention is to provide a preparation method and application of super-hydrophobic silica hydrogel for the surface of zinc-copper-titanium alloy anodic oxide film.
[0316] The core innovation of the present invention lies in that silicone oil and modifiers are used to modify the gel in the later stage of the gel preparation process to make it super hydrophobic, and the gel is roller-coated on the zinc-copper-titanium alloy anodized film to make the alloy surface film have strong corrosion resistance, thereby improving the corrosion resistance of the zinc-copper-titanium alloy anodized film.
[0317] Preparation of a novel corrosion-resistant superhydrophobic SiO2 on the surface of Zn-Cu-Ti alloy 2 The super hydrophobic SiO 2 The gel film has a black coating and its surface has a porous structure and low surface energy, so it can effectively prevent the erosion of water and other corrosive media. 2 The gel film can effectively improve its corrosion resistance and surface properties. The super hydrophobic film has a porous structure and low surface energy, which can effectively prevent the erosion of water and other corrosive media. It also has self-cleaning and anti-fouling functions, which can keep the surface clean and smooth. 2 The preparation method of gel film is simple, low-cost, and effective, and has broad application prospects.
[0318] Example 1 Superhydrophobic SiO2 for the surface of zinc-copper-titanium alloy anodic oxide film 2 Preparation method and use of hydrogel
[0319] like Figure 1 (Superhydrophobic SiO2 on the surface of zinc-copper-titanium alloy anodic oxide film 2 The preparation process of hydrogel is shown in Figure 1, which is used for the super-hydrophobic SiO2 on the surface of zinc-copper-titanium alloy anodic oxide film. 2 The preparation method and use of the hydrogel are as follows:
[0320] Dilute water glass (sodium silicate: deionized water) with deionized water, stir thoroughly for 5 minutes at 60°C to make it uniformly dispersed. Adjust the pH value of the diluted water glass to 2-3 with hydrochloric acid, and let it stand for hydrolysis for 2-24 hours, and then adjust the pH value to 6 with ammonia water.
[0321] After the gel is formed, it is first aged with water for 12-42 hours. After the aging is completed, it is centrifuged and the aging liquid is removed, and then the solvent is exchanged with anhydrous ethanol for 3 days. During this period, the ethanol is replaced at least 2-7 times, and then the replacement liquid is removed. Then, the gel is modified with a modifier (the modifier is hydroxy silicone oil or hydrogen-containing silicone oil).
[0322] After modification for a period of time, centrifuge it to remove the modification liquid, and apply the modified hydrogel roller on the surface of the alloy oxide film. The alloy is placed in a drying oven and dried at normal pressure with gradient temperature increase. (The oven is used to dry at 30°C, 60°C, 90°C, and 120°C for 0.5 hours each to obtain SiO 2 The hydrogel film was dried and then taken out to room temperature before electrochemical and other tests were performed.
[0323] It is worth noting that the modifier is added to PDMS-OH or PMHS after the acid-base two-step method, stirred evenly to make it dispersed evenly, and waited for the system to gel.
[0324] Preparation of superhydrophobic SiO by two-step acid-base method 2 The optimal process for hydrogels involves preparing SiO 2 The hydrogel film comprises the following steps: hydrolysis, aging, solvent replacement, modification, coating and drying.
[0325] The first step is hydrolysis: dilute water glass (sodium silicate) with deionized water and adjust the pH to 2-3; fully stir at 60°C for 5 minutes to evenly disperse the water glass; let it stand for hydrolysis for 2-24 hours to form a gel.
[0326] The second step is to adjust the pH with ammonia: Ammonia is used to adjust the pH to 6 to affect the balance of hydrolysis and polymerization reactions.
[0327] The third step is water aging: after the gel is formed, deionized water is used for water aging for 12-42 hours; after the aging is completed, the aging liquid is removed by centrifugation.
[0328] Step 4: Solvent replacement: Use anhydrous ethanol to replace the solvent and exchange the water in the sol; continue for 3 days and replace the ethanol at least 2-7 times to ensure effective removal of water.
[0329] Step 5: Modification: Use a modifier (hydroxy silicone oil or hydrogen silicone oil) to modify SiO 2 The hydrogel is modified; after a period of time, it is centrifuged and the modification solution is removed.
[0330] Step 6: Coating: Apply the modified SiO 2 The hydrogel is coated on the surface of the alloy oxide film using a wool roller brush or a rubber double roller.
[0331] Step 7: Drying: Place the alloy in a drying oven and dry it at a gradient temperature and normal pressure; dry it at 30°C, 60°C, 90°C, and 120°C for 0.5 hours respectively to obtain SiO 2 Hydrogel films.
[0332] Step 8. Testing: Take out the dried samples and let them stand at room temperature; perform electrochemical tests and other required tests.
[0333] In this process, deionized water, ammonia, hydrochloric acid, anhydrous ethanol, modifiers, etc. all play a key role and affect the SiO 2 The formation and properties of hydrogels. This optimal process aims to prepare SiO 2 Hydrogel film, applied to the surface of alloy oxide film.
[0334] Figure 2 Demonstrated SiO 2 Orthogonal experimental design factors and levels (seven factors and six levels) for the preparation of hydrogel coatings, showing the preparation of SiO 2 Silicone oil and modifiers were used to modify SiO 2 The hydrogel is modified to have superhydrophobic properties.
[0335] After a lot of experimental practice, the dilution ratio of sodium silicate is not less than 1:8, otherwise the acid-base two-step method for preparing SiO 2 The hydrogel process, therefore, the dilution ratio is set at 1:9-1:14; the aging treatment and solvent replacement are intended to strengthen the SiO 2 Hydrogel skeleton strength, reducing SiO 2 The tension within the hydrogel prevents the skeleton from collapsing, but after many tests it was found that it is also effective in terms of corrosion resistance, so this influencing factor can be adopted.
[0336] Example 2 Superhydrophobic SiO 2 Hydrogel
[0337] The SiO prepared in this experiment 2 Hydrogel is a colloidal dispersion system with a certain fluidity. It is an amorphous substance with a transparent or milky white appearance (such as Figure 3 As shown, SiO 2 The surface of the zinc-copper-titanium anodic oxide film sample after hydrogelation) is insoluble in water and any solvent, non-toxic and tasteless, chemically stable, and non-flammable. Figure 4 As shown, SiO 2 The surface of the zinc-copper-titanium anodized film sample after hydrogel) and the SiO 2 The hydrogel is in the form of small particles (such as Figure 5As shown, the surface of the zinc-copper-titanium anodized film sample after gradient drying).
[0338] SiO 2 The hydrogel is based on SiO 2 The skeleton forms a three-dimensional network structure of the gel that contains a large amount of water. From the inside, SiO 2 Hydrogel is a colloidal dispersion system composed of two parts: liquid and solid. It also has some properties of liquid. For example, the diffusion rate of ions in hydrogel is close to that in water. 2 In hydrogel, not only the dispersed phase (SiO 2 ) is a continuous term, and the dispersion medium (pure water) is also a continuous term. The dispersed phase forms a skeleton, forming a continuous three-dimensional network structure, which restricts the flow of water. Water transfers SiO 2 The pores of the hydrogel skeleton are completely filled.
[0339] Example 3 Superhydrophobic SiO2 for the surface of zinc-copper-titanium alloy anodic oxide film 2 Description of the hydrogel modification process
[0340] Figure 6 Demonstrated superhydrophobic SiO2 coating surface for Zn-Cu-Ti alloy anodic oxide 2 The whole fabrication process of hydrogel. SiO 2 The hydrogel modification process is described as follows:
[0341] Sodium silicate was used as a precursor, and a certain proportion of water and silicon source were uniformly mixed for dilution. After constant heating at 60°C, the system was hydrolyzed under acidic conditions to obtain a concentrated silicon precursor (H 2 SiO 3 colloid), then add ammonia water to adjust the pH under alkaline conditions, the hydrolysis and condensation reactions of the precursor proceed simultaneously, and adjusting the pH value in the solution can shift the balance of hydrolysis and polymerization of the precursor. Under acidic conditions, the hydrolysis reaction rate increases, and the precursor undergoes hydrolysis to generate silicic acid, and then the generated Si(OH) 4 The monomer undergoes a polycondensation reaction under alkaline conditions③, and finally generates a nano-network structure of SiO2 constructed by silicon-oxygen bonds (Si-O-Si). 2 Hydrogel. The sol is further cross-linked to form a wet gel with a three-dimensional network structure; the liquid in the pores of the wet gel is then removed by drying to obtain a hydrogel. To prevent the capillary force from destroying the gel network skeleton during room temperature drying, the gel must be solvent replaced and modified to enhance the structure of its network skeleton, and then subjected to room temperature gradient drying.
[0342] PMHS modification utilizes the active Si-H bond on the molecular chain to graft with -OH to form a covalent bond, which firmly covers the SiO 2The hydrogel surface is covered with hydrophilic -OH, and the -CH3 on the PMHS molecular chain is hydrophobic, making SiO 2 The hydrogel also has hydrophobic properties. Figure 7 Shown is the structural formula of PMHS modification.
[0343] PDMS-OH can be hydrolyzed to generate small molecules. The two -OH groups on the surface of the hydrolysis product can react with SiO 2 The -OH reaction on the surface of the hydrogel, the hydrolysis product of this small molecule has less steric hindrance and higher grafting rate, which can make SiO 2 The hydrogel changes from hydrophilic to hydrophobic. Figure 8 Shown is the structural formula of PDMS-OH modification.
[0344] Example 4 Electrochemical test proves that SiO 2 Corrosion resistance of zinc-copper-titanium alloy samples after hydrogel sealing
[0345] SiO 2 The corrosion resistance of zinc-copper-titanium alloy samples after hydrogel sealing has been greatly improved. This experiment has been tested through a large number of electrochemical experiments and found that its corrosion resistance trend is increasing. Fig. 9 (SiO 2 The polarization curve comparison of the hydrogel coating under other parameters is shown in the figure. The horizontal axis represents the self-corrosion current density, and the vertical axis represents the corrosion potential. The smaller the self-corrosion current density, the better the corrosion resistance trend. The larger the corrosion potential, the better the corrosion resistance. Conversely, the corrosion resistance is poor. Fig. 9 (SiO 2 Comparison of polarization curves of hydrogel-prepared coatings with other parameters). The black curve represents the unsealed sample, and the curves of different colors represent the polarization curves of samples under different process parameters. The more the curve moves toward the upper left corner, the better the corrosion resistance is, and the more it moves toward the lower right corner, the worse the corrosion resistance is. 2 With the gradual improvement of hydrogel technology, the corrosion resistance of sample film layer is increasingly enhanced, which indicates that SiO 2 The corrosion resistance of hydrogel coating applied to the surface treatment of zinc-copper-titanium alloy is feasible and the effect is as expected.
[0346] In order to more clearly show the difference in corrosion resistance trend of the surface film layer of the samples after the process, the data of the self-corrosion current density and corrosion potential of the polarization curve are listed in Fig.10 (Data table after polarization curve fitting) and plot it into a trend chart Fig.11 It can be seen that the self-corrosion current gradually decreases and the corrosion potential gradually increases, which further verifies that SiO 2 Strong corrosion resistance of hydrogel coating.
[0347] Example 5 SiO2 Pretreatment of Zn-Cu-Ti alloy before hydrogel coating and sealing (electrolytic activation of anodic oxidation)
[0348] In the pretreatment, the alloy raw material is zinc-copper-titanium alloy with a content of Zn 97.9-98.7% Cu 1-1.5% Ti0.3-0.6%; in the electrolytic activation process, the dosage, voltage, temperature and time of the activator are: 1L ultrapure water mixed with 10g NaOH as the electrolyte, the current is 50mA, the oxidation temperature is 35°C, and the oxidation time is 30min;
[0349] The process parameters of the black film layer are: 1L ultrapure water mixed with 10g NaOH as the electrolyte, the current is 50mA, the oxidation temperature is 35℃, and the oxidation time is 30min;
[0350] Process parameters of white film layer: 1L ultrapure water with 9g NaOH and 12g Na 2 CO 3 The mixture was used as the electrolyte, the current was 10A, the oxidation temperature was 30°C, and the oxidation time was 30min;
[0351] Growth of anodized film on zinc-copper-titanium alloy and dissolution of anodized film on zinc-copper-titanium alloy: The formation process of anodized film is a dynamic process of formation and dissolution. In the initial stage of the experiment, the growth of surface oxide film is dominant. Under the action of current density, the growth rate is greater than the dissolution rate, and the oxide film becomes thicker with time. As the experiment progresses, the oxide film gradually thickens and the resistance increases. The thickening of the film makes the transfer of electrolyte and electrons at the interface difficult, and the rate of film formation gradually slows down. When the growth rate of the film is equal to the dissolution rate, the thickness of the oxide film no longer increases, and the thickness of the oxide film reaches a maximum value. If the anodizing experiment continues, the film layer hinders the transfer of the medium at the interface, and the uniformity will decrease accordingly, and the surface will become rough and uneven.
[0352] The porous anodized layer only includes a porous layer, and a main component of the porous layer exists in the form of zinc oxide attached to the surface of the zinc-copper-titanium alloy.
[0353] Characteristics of porous anodized layer: The porous anodized layer is porous but loose, with irregular arrangement. The holes generated on the surface are close to the thickness of the film layer. Some holes even extend from the surface of the film layer to the surface of the substrate. Due to the existence of these pores, the external corrosive medium can penetrate the barrier layer directly into the substrate, causing the corrosion products to accumulate at the interface, reducing the corrosion resistance of the film layer.
[0354] Example 6 SiO 2 Hydrogel coating and sealing process
[0355] Modified superhydrophobic SiO 2Characterization of hydrogel coatings: modified SiO 2 The hydrogel coating will be covalently bonded to the zinc alloy substrate and can be evenly attached to the outside of the anodized layer by roller coating. The hydrophobic SiO 2 The hydrogel coating also gives the anodized film a hydrophobic property, thereby fundamentally achieving strong corrosion resistance.
[0356] In order to avoid the damage of external corrosive media to the anodic oxide film, sealing the surface of zinc-copper-titanium alloy is one of the effective anti-corrosion methods. At present, the sealing process of zinc alloy is mainly based on the sealing method of aluminum alloy. The sealing methods of aluminum alloy anodizing mainly include hydration sealing and inorganic sealing, which can effectively improve the corrosion resistance of the film layer.
[0357] When applying the sealing, use roller coating, and the roller coating equipment is a 2-inch short-hair roller brush;
[0358] The coating tool in the laboratory is a 2-inch short-haired roller brush, the size of which is 25 cm in length and 5 cm in width;
[0359] The coating tool is usually a rubber double roller of corresponding size in industrial preparation; the rubber double roller is usually made of natural rubber or synthetic rubber; the size of the rubber double roller should match the size of the material being processed, and selecting a suitable rubber double roller according to the size of the zinc-copper-titanium alloy material can improve the uniformity and efficiency of coating; the rubber double roller should be a rubber double roller with a smooth and flawless surface to improve the quality and effect of coating; the rubber double roller should be a rubber double roller with appropriate elasticity to ensure that the coated hydrogel has good adhesion and uniformity. The hardness of the rubber double roller should match the hardness of the material being processed to ensure the effect and quality of coating.
[0360] In SiO 2 After the hydrogel is modified, the zinc-copper-titanium alloy anodized film can be roller-coated with a roller brush for 1-3 times to ensure uniformity, and then placed in a drying oven for gradient drying. There is no fixed requirement for the dosage of each coating. After coating, the gel remaining on the surface of the oxide film is relatively small, and the dosage is 1g. Roll coating 1-3 times, with an interval of 10 minutes in between, in order to fully combine the gel with the substrate, but the effect of too many coating times is not obvious, so the preferred solution is to roll coating twice, with an interval of 10 minutes in between.
[0361] Example 7 SiO 2 Hydrophobicity test of hydrogel
[0362] SiO 2The most fundamental principle of using hydrogel in the surface treatment of zinc-copper-titanium alloy anodized film is that it has super-hydrophobic properties. The most direct method to test hydrophobicity is the hydrophobic angle test. This experiment preliminarily verified through actual pictures that it does greatly improve the corrosion resistance.
[0363] Fig.12 This is a side view of the surface hydrophobicity of the zinc-copper-titanium alloy sample, to roughly observe the difference in hydrophobicity. Sample (a) is an unsealed sample, and its hydrophobic angle is roughly estimated to be 42.4°, and the droplet has strong adhesion to the surface film layer. The sample under the unsealed process is hydrophilic; sample (b) is a gel-coated sample, and its hydrophobic angle is roughly estimated to be 83°. Due to the influence of the droplet gravity, the normal hydrophobic angle should be greater than 90°, and the sample is slightly tilted, and the droplet will slide along the surface, and the adhesion to the surface is very small. Therefore, the surface film layer of the sample after gel sealing is hydrophobic, which is in line with the expectations of the experimental results. It is precisely because the gel film layer is hydrophobic that it fundamentally isolates large-area contact with water, and then blocks the damage to the surface by chloride ions in seawater or the atmosphere, thus achieving the purpose of high corrosion resistance.
[0364] Fig.13 Super hydrophobic SiO2 on the surface of zinc-copper-titanium alloy anodic oxide film 2 Film ratio table. The results in this table are obtained based on the water contact angle tester and tested in accordance with the industry standard. The ratio in the first example of the table refers to the increase rate of the hydrophobic angle of the growing test sample and the control sample.
Claims
1. A method for preparing a super-hydrophobic SiO2 hydrogel on the surface of a zinc-copper-titanium alloy anodized film, characterized in that: The preparation method includes obtaining a wet gel by an acid-base two-step method with sodium silicate, then exchanging the wet gel with an ethanol solvent, and modifying the wet gel with a hydroxy silicone oil PDMS-OH or a hydrogen-containing silicone oil PMHS as a modifier, thereby obtaining a super-hydrophobic SiO2 hydrogel suitable for an anodic oxidation film of a zinc-copper-titanium alloy; the specific steps are as follows: Step (1), hydrolysis of sodium silicate: 1) Using sodium silicate as a precursor, uniformly mixing it with water and a silicon source in a specific ratio; 2) heating the mixed system at a constant temperature of 60° C. to allow the system to undergo a hydrolysis reaction under acidic conditions; 3) Hydrolysis to generate silicic acid and other pre-products; Step (2), obtaining silicon precursor H2SiO3 colloid: After the hydrolysis reaction, a concentrated silicon precursor H2SiO3 colloid is formed, which contains silicic acid and related substances; Step (3), polycondensation reaction under alkaline conditions: 1) Under alkaline conditions, the pH value of the solution is adjusted by adding ammonia water; 2) The silicon precursor undergoes a polycondensation reaction to generate Si(OH)4 monomer; 3) Si(OH)4 monomers further condense under alkaline conditions to form a nano-network structure constructed by silicon-oxygen bonds Si-O-Si; 4) The formation of SiO2 wet gel, the formed SiO2 hydrogel nano-network structure constitutes the basis of the wet gel; the SiO2 wet gel has a three-dimensional network structure, which still contains liquid that needs to be subsequently processed; Step (4), adding pure water to the gel system for aging: 1) Add pure water H2O to the sol system, allow the system to age, and keep it for a period of time to promote the reaction; 2) The sol is further cross-linked to form a wet gel with a three-dimensional network structure; Step (5), solvent replacement and modification: 1) Add ethanol C2H5OH to the sol system and drain the water; 2) Using organic matter containing silicon to modify the surface of SiO2 hydrogel; The modifier used for surface modification is hydroxy silicone oil PDMS-OH or hydrogen silicone oil PMHS; Step (6), drying to prepare SiO2 hydrogel: 1) After the wet gel is formed, drying is performed to remove the liquid in the pores of the wet gel, and finally a SiO2 hydrogel is obtained; 2) Prevent capillary forces from destroying the gel network skeleton during room temperature drying.
2. The preparation method according to claim 1, characterized in that: The super-hydrophobic SiO2 hydrogel used for the surface of the zinc-copper-titanium alloy anodized film in steps (1) to (3) is treated by an acid-base two-step method; After step (1), the sodium silicate solution needs to be dropwise added with 36-38% hydrochloric acid using a rubber dropper while stirring; the pH is adjusted to 2-3, at which time the addition of hydrochloric acid is stopped; The acidic regulator in the acidification reaction is 36-38% hydrochloric acid HCl, and the dosage of hydrochloric acid is 10-25 mL. After the acidification reaction, the product needs to be allowed to stand for hydrolysis for 2 to 24 hours to help form silicate ions.
3. The preparation method according to claim 2, characterized in that: The super-hydrophobic SiO2 hydrogel used for the surface of the zinc-copper-titanium alloy anodized film in steps (1) to (3) is treated by an acid-base two-step method; After the acidification reaction, the sodium silicate solution was added dropwise with 25% ammonia water using a rubber-tipped dropper while stirring; the pH value of the gel was adjusted to 6, at which time the addition of ammonia water was stopped; The alkaline regulator in the alkalization reaction is 25% ammonia NH3H2O, and the ammonia dosage is 10-25mL. The addition amount of the modifier hydroxy silicone oil PDMS-OH or hydrogen silicone oil PMHS is in the range of 20% to 60% of the gel volume.
4. The preparation method according to claim 3, characterized in that: The dosage of hydrochloric acid in the acidification reaction is set to 15 mL; the dosage of ammonia water, the alkaline regulator, in the alkalization reaction is 8 mL, and the addition amount of the modifier hydroxy silicone oil PDMS-OH or hydrogen silicone oil PMHS is 40% of the gel volume.
5. The preparation method according to claim 1, characterized in that In step (4), the super-hydrophobic SiO2 hydrogel on the surface of the zinc-copper-titanium alloy anodized film is subjected to an aging treatment; The aging treatment is to allow the solution system to age, that is, to maintain it for a period of time; The aging time is 12-42 hours, which fully allows the cross-linking reaction to proceed fully, forming a more stable three-dimensional network structure and improving the mechanical strength and stability of the wet gel. After aging, the aging liquid is centrifuged and removed.
6. The preparation method according to claim 5, characterized in that During the aging process, the sol is further cross-linked to form a wet gel with a more stable three-dimensional network structure, thereby increasing the mechanical strength and solvent resistance of the SiO2 wet gel and maintaining the high specific surface area and pore structure of the wet gel. After aging, the sol is centrifuged and the aging liquid is removed.
7. The preparation method according to claim 1, characterized in that The step (5) is to subject the super-hydrophobic SiO2 hydrogel on the surface of the zinc-copper-titanium alloy anodized film to solvent replacement treatment; The solvent replacement treatment uses anhydrous ethanol as a replacement solvent, which is added to the sol-gel system formed in the previous step; the anhydrous ethanol can avoid the introduction of additional water; The dosage of anhydrous ethanol as the replacement solvent is not less than 1:1; The solvent replacement treatment has an exchange time of 3 days.
8. The preparation method according to claim 1 or 2, characterized in that The step (5) is to subject the super-hydrophobic SiO2 hydrogel on the surface of the zinc-copper-titanium alloy anodized film to solvent replacement treatment; The solvent replacement process replaces the anhydrous ethanol solvent at least 2 to 7 times during the exchange period; After the solvent exchange is completed, the ethanol replacement solution is removed by separation methods such as centrifugation and filtration.
9. The preparation method according to claim 1, characterized in that: The super-hydrophobic SiO2 hydrogel on the surface of the zinc-copper-titanium alloy anodized film in step (5) is subjected to a modification treatment; The modification treatment comprises gradually adding a selected modifier to the gel to ensure uniform mixing; stirring or standing for a period of time; and the modifier and the gel undergo corresponding chemical reaction or physical adsorption.
10. The preparation method according to claim 9, characterized in that: The modification treatment includes stirring or standing for 30 to 60 minutes to allow the modifier to fully contact the gel; The addition amount of the modifier hydroxy silicone oil PDMS-OH or hydrogen silicone oil PMHS is in the range of 20%-60% of the gel volume.
11. The preparation method according to claim 9 or 10, characterized in that: The super-hydrophobic SiO2 hydrogel on the surface of the zinc-copper-titanium alloy anodized film in step (5) is subjected to a modification treatment; The modification treatment uses a centrifuge to centrifuge the modified gel to separate the gel and the modifier; the amount of the modifier hydroxy silicone oil PDMS-OH or hydrogen silicone oil PMHS added is 40% of the gel volume, and the centrifugal conditions are as follows: the centrifugal time is not less than 30 min / kg and the centrifugal speed is 3600 rpm.
12. The preparation method according to claim 1, characterized in that: The raw material silicon precursor is 35% industrial grade sodium silicate solution.
13. Use of super-hydrophobic SiO2 hydrogel on the surface of zinc-copper-titanium alloy anodic oxide film prepared by the method of claim 1, characterized in that: The surface of the zinc-copper-titanium alloy anodized film after anodization is coated and sealed with the specially prepared SiO2 hydrogel to form a super-hydrophobic functional black coating on the surface of the zinc-copper-titanium alloy anodized film, so that the static contact angle is not less than 120°. The hydrophobic SiO2 hydrogel film has a black coating, and its surface has a porous structure and low surface energy.
14. The use according to claim 13, characterized in that The steps of coating and sealing the surface of the zinc-copper-titanium alloy anodized film after anodizing are as follows: Step (1), pre-treatment of the anodic oxide film of the zinc-copper-titanium alloy: the zinc-copper-titanium alloy is subjected to casting, cutting, electrolytic activation, and substrate cleaning, thereby forming an anodic oxide film on the surface of the zinc-copper-titanium alloy; Step (2), preparing the prepared SiO2 hydrogel and inspecting and ensuring that it has appropriate properties; Step (3), coating and sealing the surface of the zinc-copper-titanium alloy anodized film with the prepared SiO2 hydrogel, ensuring that the surface of the zinc-copper-titanium alloy anodized film is completely covered with the SiO2 hydrogel; and waiting for a certain period of time to ensure that the SiO2 hydrogel fully penetrates and covers the surface of the anodized film; Step (4), drying the zinc-copper-titanium alloy anodized film sample coated with SiO2 hydrogel to remove excess solvent and water, so that the SiO2 hydrogel forms a uniform black coating on the surface, i.e., a super-hydrophobic SiO2 hydrogel film on the surface of the zinc-copper-titanium alloy; Step (5), checking the uniformity and integrity of the coating to ensure the sealing effect; Step (6), in order to ensure the uniform effect of the zinc-copper-titanium alloy anodized film coating, repeat the coating step to adjust the thickness of the coating; Step (7), gradient drying the super hydrophobic SiO2 hydrogel film on the surface of the zinc-copper-titanium alloy.
15. The use according to claim 13, characterized in that The zinc-copper-titanium alloy obtained after the anodizing treatment has completed the pre-treatment of the oxide film, and the pre-treatment is the electrolytic activation treatment of the zinc-copper-titanium alloy anodizing, including: placing the zinc-copper-titanium alloy in an electrolytic activation solution, using the zinc-copper-titanium alloy as an anode, a lead plate as a cathode, applying direct current, and forming an electrolytic cell with NaOH as an electrolyte; then taking out the zinc-copper-titanium alloy and washing it with water; Calculated by mass percentage, the raw material ratio of the zinc-copper-titanium alloy is 89.5% zinc Zn, 1% copper Cu, and 0.5% titanium Ti; In terms of mass percentage, the anodizing solution includes: 1 L of ultrapure water mixed with 10 g of NaOH in volume percentage.
16. The use according to claim 15, characterized in that The pre-treatment is an electrolytic activation treatment for anodizing the zinc-copper-titanium alloy, including: the current for the anodizing electrolytic oxidation treatment is 50 mA; the oxidation temperature for the anodizing electrolytic oxidation treatment is 35° C.; The oxidation time for the anodic oxidation electrolytic oxidation treatment is 30 minutes; In the electrolytic cell, an oxidation reaction occurs at the anode and a reduction reaction occurs at the cathode; The anode zinc-copper alloy loses electrons and undergoes oxidation reaction to form metal ions Zn 2+ Cu 2+ Ti 4+ into the electrolyte; The cathode lead plate will gain electrons, undergo a reduction reaction, and form hydrogen H2.
17. The use according to claim 13, characterized in that The coating comprises roller coating the zinc-copper-titanium alloy anodic oxide film with a roller brush; The coating comprises: using the prepared SiO2 hydrogel, after each coating, leaving the porous zinc-copper-titanium alloy oxide layer to stand for 10 minutes, and then coating again, and repeating the operation 1-3 times; The coating tool is a 2-inch short-hair wool thumb roller brush or a rubber double roller, and the size of the roller brush is 5 to 10 cm in diameter and 8 cm in width.
18. The use according to claim 17, characterized in that The coating dosage is 1g of SiO2 hydrogel; the coating times include two roller coatings, with a 10-min standstill in between; The coating is then followed by gradient drying.
19. The use according to claim 18, characterized in that The gradient drying comprises drying the super-hydrophobic SiO2 hydrogel film on the surface of the zinc-copper-titanium alloy after coating and sealing in a drying oven; The drying process is carried out in a drying oven by gradient temperature increase and normal pressure drying to obtain a SiO2 hydrogel film, which needs to be taken out of the drying oven after drying and allowed to cool to room temperature.
20. The use according to claim 19, characterized in that The gradient drying process is performed 4 times; the temperatures of the 4 drying processes are respectively 30° C., 60° C., 90° C., and 120° C.; The duration of the four drying treatments is 0.5 hours each time.
21. The use according to claim 20, characterized in that After the four drying treatments, the SiO2 hydrogel film on the surface of the zinc-copper-titanium alloy is obtained, and after drying, it needs to be taken out from the drying oven and wait for room temperature; The SiO2 hydrogel film on the surface of the zinc-copper-titanium alloy obtained after the four drying treatments needs to be subjected to electrochemical testing, and the test results show that the static contact angle of the SiO2 hydrogel film is not less than 120°.
Citation Information
Patent Citations
Surface treatment method of metal with anodic oxide film and metal
CN110760912A
Hydrophobic material
CN1378581A